Produção de cerâmica de revestimento utilizando resíduos de rochas ornamentais provenientes do tear de fio diamantado - Gomes, Tiago Marvila (2017)
Brazil is one of the largest producers of dimension stones in the world. Besides the economic advantages brought by the sector, there is also the generation of significant amount of fine solid wastes. The composition of these wastes shows the possibility of using them in several products, such as in manufacture of ceramic coating. The aim of this work was to use dimension stone waste from the diamond wire loom for production of ceramic coating. Compositions were prepared containing 40%, 50% and 60% of waste in the ceramic base, which were characterized regarding to the crystalline phase, particle size distribution and plasticity. Ceramic plates were sintered at 1100 °C and analyzed concerning to density, linear shrinkage and water absorption. Glazes were prepared with 40, 45 e 50 % of waste. Using these glazes and the base ceramic, ceramic coating were prepared and analyzed visually regarding to adhesiveness and chemical attack. Wettability test was carried out using the Sessile Drop method, that evolve the fusion of glazed proof bodies with 3 mm x 3 mm x 3 mm on sintered red ceramic with 30 mm x 30 mm x 5 mm. The contact angle was measured during fusion of the glazed material and the results were treated through factorial 22 analysis. The results indicate that the studied compositions have potential for industrial applications, presenting water absorption values close to 10%, contact angles - of the glaze in the base ceramic - smaller than 45° and a good adherence of the ceramic coating.